2005
DOI: 10.1152/physiolgenomics.00249.2004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a molecular signature of sarcopenia

Abstract: Investigating the molecular mechanisms underlying sarcopenia in humans with the use of microarrays has been complicated by low sample size and the variability inherent in human gene expression profiles. We have conducted a study using Affymetrix GeneChips to identify a molecular signature of aged skeletal muscle. The molecular signature was defined as the set of expressed genes that best distinguished the vastus lateralis muscle of young ( n = 10) and older ( n = 12) male subjects, when a k-nearest neighbor su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
153
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(167 citation statements)
references
References 70 publications
10
153
0
4
Order By: Relevance
“…52 These studies suggest that the association between Atrogin-1 and muscle atrophy may be fiber type-or gender-dependent. Another explanation could be that sarcopenia is mechanistically different from acute muscle atrophy, which is marked by increased expression of Atrogin-1, as suggested by Edstrom et al 51 This statement is supported by the findings of Giresi and colleagues, 45 who conducted a microarray study with muscle samples from 19-25-yr-old and 70-80-yr-old male subjects to identify the molecular signature of sarcopenia.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…52 These studies suggest that the association between Atrogin-1 and muscle atrophy may be fiber type-or gender-dependent. Another explanation could be that sarcopenia is mechanistically different from acute muscle atrophy, which is marked by increased expression of Atrogin-1, as suggested by Edstrom et al 51 This statement is supported by the findings of Giresi and colleagues, 45 who conducted a microarray study with muscle samples from 19-25-yr-old and 70-80-yr-old male subjects to identify the molecular signature of sarcopenia.…”
Section: Discussionmentioning
confidence: 74%
“…High density oligonucleotide microarrays have previously been utilized to characterize, e.g., age-or exercise-related changes in human skeletal muscle, [40][41][42][43][44][45][46][47][48][49] but not directly menopause-or HRT-related transcriptional changes. The transcriptome-wide effects of HRT have only been studied in blood samples from postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptional networks altered with aging have been well characterized (Giresi et al ., 2005); however, whether global changes in the expression of genes related to muscle regeneration play a causative or compensatory role in age‐related defective muscle regeneration remains an unanswered question.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report using microarray analysis comparing muscle biopsies in 10 young versus 12 older subjects found that muscle from older subjects demonstrated differences associated with apoptosis, such as increased complement component C1QA, galectin-1, C/EBP-b and FOXO-3A expression -findings considered as a 'molecular signature' of sarcopenia (Giresi et al 2005). A decline in anabolic hormones and reduction in myonuclei via apoptotic-like mechanisms represent alternative explanations for sarcopenia (Leeuwenburgh 2003).…”
Section: Sarcopeniamentioning
confidence: 99%